Pengaruh Edukasi Terhadap Tingkat Pengetahaun Remaja Tentang Penyakit Menular Seksual di Kelas XI SMA Negeri 21 Medan - Marpaung, Adhar Zulfikar; Silaen, Harsudianto (Indonesian Trust Nursing Journal, 2025)
Sexually Transmitted Diseases (STDs) are diseases that are transmitted through sexual intercourse, either through the vagina, mouth, or anus, sexually transmitted diseases are still a public health problem throughout the world, both in developed and developing countries, One factor that can influence the occurrence of sexually transmitted diseases is knowledge. One effort that can be made to increase knowledge about handling sexually transmitted diseases isby providing health education, The purpose of this study is the Effect of Education on the Level of Knowledge of Adolescents About Sexually Transmitted Diseases in Class XI of SMA Negeri 21 Medan. This type of research is quantitative which is a pre-experimental study with a one group pre-posttest design using a total sampling technique. The number of samples in this study was 300 female students, but when the study was conducted, 237 respondents were present, so the sample in this study was 237 respondents with a p-value of 0.001 (α0.05) which indicates that there is a significant influence of education using the lecture method on the level of knowledge of adolescents about sexually transmitted diseases. It can be concluded that there is an influence of education on the level of knowledge of adolescents about sexually transmitted diseases. It is recommended to conduct further research by adding different variables such as the relationship between knowledge and attitudes and behaviors in preventing sexually transmitted diseases.